Experimental study on directional motion of a single droplet on cactus spines. (May 2015) - Guo, L.; Tang, G.H.
Abstract: Cactus spines are found to have high efficiency of fog collection. The ability in rapidly driving droplets could be applied in the condensation process to refresh the heat transfer area and improve the heat transfer coefficients. The self-driven process of a single droplet on cactus spines is experimentally and theoretically studied. Both Newtonian droplet and shear-thinning non-Newtonian droplet move directionally from the tip to the base owing to the decreased Gibbs free energy along the spine. The shear-thinning non-Newtonian droplet moves slower because of the increased viscosity loss. The maximum velocity observed in the experiment for water droplet is 1.17 m/s, exhibiting the high efficiency of conical spines on driving drops.